The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acs.biochem.5b01300
|View full text |Cite
|
Sign up to set email alerts
|

Competence of Thiamin Diphosphate-Dependent Enzymes with 2′-Methoxythiamin Diphosphate Derived from Bacimethrin, a Naturally Occurring Thiamin Anti-vitamin

Abstract: Bacimethrin (4-amino-5-hydroxymethyl-2-methoxypyrimidine), a natural product isolated from some bacteria, has been implicated as an inhibitor of bacterial and yeast growth, as well as in inhibition of thiamin biosynthesis. Given that thiamin biosynthetic enzymes could convert bacimethrin to 2′-methoxythiamin diphosphate (MeOThDP), it is important to evaluate the effect of this coenzyme analogue on thiamin diphosphate (ThDP)-dependent enzymes. The potential functions of MeOThDP were explored on five ThDP-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Anerobic conditions were established either in a Baker-Ruskinn in vivo (Sanford, ME) or a Coy Laboratory Products vinyl anaerobic chamber (Grass Lake, MI). E. coli WT DXP synthase and E. coli MEP synthase (IspC) were overexpressed and purified as reported previously with minor modifications for the purification of anaerobic DXP synthase (14,34). To obtain anaerobic DXP synthase, the protein was overexpressed and purified as previously described (34), however, the second dialysis was carried out in an anaerobic chamber in 50 mM HEPES, pH 8, 5% glycerol, 100 mM NaCl, 10 mM MgCl 2 , and 1 mM ThDP at 0°C for 4 h. The protein was stored in liquid N 2 until use when it was transferred directly to an anaerobic chamber.…”
Section: General Methodsmentioning
confidence: 99%
“…Anerobic conditions were established either in a Baker-Ruskinn in vivo (Sanford, ME) or a Coy Laboratory Products vinyl anaerobic chamber (Grass Lake, MI). E. coli WT DXP synthase and E. coli MEP synthase (IspC) were overexpressed and purified as reported previously with minor modifications for the purification of anaerobic DXP synthase (14,34). To obtain anaerobic DXP synthase, the protein was overexpressed and purified as previously described (34), however, the second dialysis was carried out in an anaerobic chamber in 50 mM HEPES, pH 8, 5% glycerol, 100 mM NaCl, 10 mM MgCl 2 , and 1 mM ThDP at 0°C for 4 h. The protein was stored in liquid N 2 until use when it was transferred directly to an anaerobic chamber.…”
Section: General Methodsmentioning
confidence: 99%
“…The overall activity of PDHc containing either WT or ␣V138M E1 was measured by monitoring the formation of NADH (and H ϩ ) at 340 nm, as reported previously (22). PDHc was reconstituted by premixing the E1, E2⅐E3BP, and E3 proteins at a microgram mass ratio of 1:3:3 in a buffer of 50 mM KH 2 PO 4 (pH 7.0) and 0.15 M NaCl for 60 min at 25°C (31).…”
Section: Enzyme Activity Measurementsmentioning
confidence: 99%
“…1). The design principles and general modus operandi of these antivitamins are highly similar as they all bear a small chemical modification of the vitamin scaffold, are taken up by the target species in the form of a modified precursor and are eventually transformed by the native downstream machinery responsible for biosynthesis of the biologically active cofactor form, often with higher affinity than the native cofactor, to yield the mature cofactor analog [6][7][8][9][10][11] .…”
mentioning
confidence: 99%
“…A set of enzyme targets for MThDP was identified in E. coli, namely α-ketoglutarate dehydrogenase, transketolase (TK) and 1-deoxy-d-xylulose-5 -phosphate synthase (DXS). In vitro studies on several ThDP enzymes demonstrated that the enzymatic activities of both E. coli pyruvate dehydrogenase (EcPDH) and E. coli 1-deoxy-d-xylulose-5 -phosphate synthase are strongly inhibited upon reconstitution with MThDP 11 . Conversely, E. coli α-ketoglutarate dehydrogenase and human PDH retain almost full enzymatic activity with MThDP as the cofactor 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation